2001
DOI: 10.1002/1097-0142(20011115)92:10<2585::aid-cncr1611>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy followed by tumor debulking prolongs survival for patients with poor prognosis in International Federation of Gynecology and Obstetrics Stage IIIC ovarian carcinoma

Abstract: BACKGROUND Patients with advanced ovarian carcinoma of International Federation of Gynecology and Obstetrics (FIGO) Stage IIIC should be treated by radical surgical tumor debulking with the goal of complete tumor resection. Prolonged median survival can be achieved in those patients entirely free of tumor after surgery by the administration of postsurgical platinum/taxane‐based chemotherapy regimens. However, residual tumor is present in the majority of patients, which limits survival prognosis. Different ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(96 citation statements)
references
References 23 publications
(26 reference statements)
5
85
1
5
Order By: Relevance
“…Similar to our findings, Giannopoulos and colleagues [16] found lower mean blood loss in NAC group. Unlike our findings, Kuhn et al [25] and Yan and colleagues [26] found no difference in need for transfusion and intraoperative bleeding.…”
contrasting
confidence: 99%
“…Similar to our findings, Giannopoulos and colleagues [16] found lower mean blood loss in NAC group. Unlike our findings, Kuhn et al [25] and Yan and colleagues [26] found no difference in need for transfusion and intraoperative bleeding.…”
contrasting
confidence: 99%
“…Neoadjuvant chemotherapy decreases tumor volume and facilitates surgical procedures especially chemosensitive tumor which had completed or partial clinical response achievement in 76% of patients with less residual volume which had an impact of decrease morbidity and mortality and improving clinical outcome [16]- [23]. Analysis of our data showed significant improvement in both progression-free survival and overall survival in those underwent NACT-IDS compared to PDS-ACTR these results comparable to those published by Kuhn et al [24] [25], Rose et al, and Muggia et al [6] [24] [25] [26], they showed prolonged survival times and significantly better median survival in NACT group than the conventional PDS-ACTR. According to data published by Onnis et al [18] and Surwit et al…”
Section: A H Zaky Et Alsupporting
confidence: 85%
“…Other studies also reported that patients who underwent NAC/IDS had lower estimated blood loss and shorter OR time and hospital stay (12,14,20). Only a few studies found no difference in perioperative morbidity between the NAC/ IDS and PDS groups (4).…”
Section: Discussionmentioning
confidence: 96%
“…The effect of NAC/IDS on survival and perioperative morbidity varies in these studies (4)(5)(6). According to these studies, patients treated with NAC/IDS had comparable survival with those who underwent PDS (5,(7)(8)(9).…”
Section: Original Articlementioning
confidence: 98%
See 1 more Smart Citation